Preparation of Terephthalate Plasticizers based on Oxyma Low Temperature Activation - Siyu PAN; Tian LU; Demeng LIU; Delong HOU; Xianchong SUN; Yi CHEN (Pige Kexue Yu Gongcheng)
Terephthalate, an effective alternative to traditional highly toxic phthalate plasticizers, has gradually become one of the fastest-growing environmentally friendly plasticizer in recent years. However, conventional Fischer synthesis methods require temperatures above 200 ℃, resulting in high energy consumption and stringent equipment requirements. Here, using terephthalic acid and butanol as a representative, this work explored the feasibility of synthesizing dibutyl terephthalate at lower temperature by Oxyma activation method. The reaction conditions were optimized by using the response surface methodology. It was demonstrated that the yields of terephthalates with alcohol carbon chain lengths of 4-10 prepared could be more than 96.5% under the optimal reaction conditions, i.e., reacting at 33 ℃ for 11.7 h under n(terephthalic acid)∶n(butanol)∶n(Oxyma)=1∶3∶0.81. Furthermore, this study also examined the suitability of the above synthesis technique for regenerating terephthalic acid. The present efforts may provide a technical support for reducing energy consumption in the production of terephthalate plasticizers, and give a reference for the high-value use of recycled terephthalic acid.